2004
DOI: 10.1590/s0037-86822004000400001
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças clínicas observadas em pacientes com dengue causadas por diferentes sorotipos na epidemia de 2001/2002, ocorrida no município do Rio de Janeiro

Abstract: The authors evaluated clinical and epidemiological differences among the serotypes of dengue in Rio de Janeiro's 2001-2002 outbreak of the disease. Out of 362 cases that had viral isolation samples, notified by the Information System for Notification Diseases (SINAN), from January/2001 to June/2002, 62 were caused by serotype 1,62 by serotype 2 and 238 by serotype 3. In comparison with serotype 2, an individual infected by serotype 3 had a 6.07 times higher chance (OR = 6.07; CI: 1.10-43.97) of presenting shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…These levels are considerably lower than the levels observed in Bangkok (80%–90%) and Jakarta (49%) (26). A study on clinical differences observed in patients with dengue caused by DENV-3 showed that they had 3.06 times more risk for abdominal pain than patients with DENV-1 and 6.07 times more risk for shock than patients infected with DENV-2 (28). …”
Section: Discussionmentioning
confidence: 99%
“…These levels are considerably lower than the levels observed in Bangkok (80%–90%) and Jakarta (49%) (26). A study on clinical differences observed in patients with dengue caused by DENV-3 showed that they had 3.06 times more risk for abdominal pain than patients with DENV-1 and 6.07 times more risk for shock than patients infected with DENV-2 (28). …”
Section: Discussionmentioning
confidence: 99%
“…Segundo Passos e cols 18 , indivíduos acometidos pelo DENV 3 apresentam sintomatologia mais grave, apresentando chance 6,07 vezes maior de apresentar choque em relação aos indivíduos infectados com DENV 2, sugerindo maior virulência deste sorotipo. Este fato nos permite concluir que a população de Manaus poderia vir a apresentar um maior número de casos graves da doença, uma vez que todos os mosquitos infectados o estavam pelo DENV 3.…”
Section: Discussionunclassified
“…O processo de urbanização desordenado com grande aglomeração populacional, as deficiências no suprimento de água, o tratamento de esgoto inexistente ou inadequado e a ausência de destino adequado do lixo com o acúmulo de recipientes plásticos não biodegradáveis contribuem para essa situação. Além disso, a facilidade de transporte e as intensas relações comerciais entre regiões, permitindo a entrada de pessoas infectadas em período de incubação ou mesmo do vetor em localidades indenes, e a falência dos programas de controle do mosquito favorecem o aumento da transmissão do dengue (16) . Essa situação também é encontrada na região do Grande ABC, onde todas as características citadas estão presentes e condicionam o aparecimento da doença.…”
Section: Introductionunclassified